Proses Pemurnian Minyak Jelantah Menggunakan Metode Adsorbsi Kolom - Abdan Syakura; Halim Zaini; Syafruddin Syafruddin (Politeknik Negeri Lhokseumawe, 2025)
Cooking oil is one of the basic human needs as a food processing ingredient. Using cooking oil repeatedly and continuously during thefrying process will reduce the quality of the cooking oil. One way to process used cooking oil is by adsorption using an activated carbonadsorbent. In this research, adsorbents used sugar cane bagasse, rice husks and coconut fiber were used using the column adsorptionmethod. Also, with sampling times of 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100 (minutes). This research aims to determine the comparativeeffect of adsorbent variations and the effect of adsorption time on the reduction of free fatty acids, water content, peroxide value and density. Sugarcane bagasse, rice husks and coconut fiber were activated using 0.1 N NaOH for 2 hours, where the activation aims to increasethe pore diameter or produce new pores. The results of the research that has been carried out are that the best reduction in free fatty acidswas in the rice husk adsorbent type with an adsorption time of 90 minutes, resulting in free fatty acids of 1.84%. And the best peroxidevalue obtained was 6.6 mg/g. From the results of this research it can be concluded that rice husk adsorbent is better in reducing free fattyacids and peroxide value using the column adsorption method.